Optimizing the Detection of Venous Invasion in Colorectal Cancer: The Ontario, Canada, Experience and Beyond - Dawson, Heather; Kirsch, Richard; Driman, David K.; Messenger, David E.; Assarzadegan, Naziheh; Riddell, Robert H. (Frontiers in Oncology, 2015)
Venous invasion (VI) is a well-established independent prognostic indicator in colorectal cancer (CRC). Its accurate detection is particularly important in stage II CRC as it may influence the decision to administer adjuvant therapy. The Royal College of Pathologists (RCPath) of the United Kingdom state that VI should be detected in at least 30% of CRC resection specimens. However, our experience in Ontario, Canada suggests that this (conservative) benchmark is rarely met. This article highlights the “Ontario experience” with respect to VI reporting and the key role that careful morphologic assessment, elastin staining and knowledge transfer has played in improving VI detection provincially and beyond.